2020
DOI: 10.3390/cancers12051089
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Rationale for Combined Immunotherapy with PD-1/PD-L1 Antibodies and VEGF Inhibitors in Advanced Hepatocellular Carcinoma

Abstract: A successful phase III trial for the combination of atezolizumab and bevacizumab (the IMbrave150 trial) in advanced hepatocellular carcinoma has recently been reported. This is groundbreaking because nivolumab and pembrolizumab, both programmed cell death-1 (PD-1) antibodies, have failed to show efficacy as first- and second-line therapeutics, respectively, in phase III clinical trials. Immunotherapy with a combination of atezolizumab and bevacizumab resulted in better survival than treatment with sorafenib fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
140
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(143 citation statements)
references
References 69 publications
3
140
0
Order By: Relevance
“…A recent phase 1b study showed that the objective response rate (ORR; according to RECIST version 1.1) of atezolizumab plus bevacizumab (arm A) was 36% [40], which was markedly higher than the ORR (RECIST version 1.1) of nivolumab monotherapy and pembrolizumab monotherapy (15-18.3%) [20,21]. This is attributed to the fact that anti-VEGF therapy improves the recruitment of DC, the activation of CD8 + T cells, and trafficking and infiltration of CD8 + T cells into the tumor tissue and improves immunosuppressive TME in the immune moderate subclass [39] (Fig. 5, 7).…”
Section: Possible Treatment Strategy For the Immune Subclass Includinmentioning
confidence: 88%
See 1 more Smart Citation
“…A recent phase 1b study showed that the objective response rate (ORR; according to RECIST version 1.1) of atezolizumab plus bevacizumab (arm A) was 36% [40], which was markedly higher than the ORR (RECIST version 1.1) of nivolumab monotherapy and pembrolizumab monotherapy (15-18.3%) [20,21]. This is attributed to the fact that anti-VEGF therapy improves the recruitment of DC, the activation of CD8 + T cells, and trafficking and infiltration of CD8 + T cells into the tumor tissue and improves immunosuppressive TME in the immune moderate subclass [39] (Fig. 5, 7).…”
Section: Possible Treatment Strategy For the Immune Subclass Includinmentioning
confidence: 88%
“…ICI monotherapy is not effective in HCC of the immune exclusion type with activating WNT/β-catenin mutation; however, it remains unclear whether combination therapies (e.g., anti-PD-1/PD-L1 therapy plus anti-CTLA-4 therapy or anti-PD-1/PD-L1 therapy plus anti-VEGF/MTA therapy) [35][36][37] can alter the TME and induce a change from immune suppressive to immune permissive even in β-catenin-mutated HCC [38,39], which would revert the decreased DC recruitment and CD8 + T-cell infiltration into tumors caused by β-catenin activation. These issues need to be confirmed in future studies.…”
Section: Possible Treatment Strategy For the Immune Subclass Includinmentioning
confidence: 99%
“…Since its approval in 2007, the multi-tyrosine kinase inhibitor (TKI) sorafenib remained the standard of care in patients with advanced HCC for over a decade. Only recently, lenvatinib was shown non-inferior to sorafenib [ 6 ], and even more importantly, the combination of atezolizumab plus bevacizumab improved both co-primary endpoints overall survival (OS) and progression-free survival (PFS) compared to sorafenib, and thus will become the new frontline treatment [ 7 , 8 , 9 ]. Nevertheless, sorafenib will still play a crucial role in the treatment algorithm of HCC, as all currently approved second-line treatments (regorafenib, cabozantinib, ramucirumab) have been approved in sorafenib-experienced patients [ 5 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, in addition to typically immunomodulatory molecules such as PD-1/PD-L1 and CTLA-4, VEGF has emerged as an interesting target. Besides its role in angiogenesis, VEGF has important immunomodulatory properties, such as its inhibitory role in dendritic cells and the recruitment of immunosuppressive subsets, among others [ 40 ], transforming thus the tumor microenvironment. Indeed, it has been recently reported in a preclinical HCC model [ 41 ] that dual PD-1 and VEGFR blockade increases CD8 T-cell infiltration, associated with a higher therapeutic efficacy, suggesting that vaccine-induced T-cells may benefit from this property of VEGF blockade.…”
Section: Discussionmentioning
confidence: 99%